Stroke in the young adult - Saver, Jeffrey (Henry Stewart Talks, 2008)
Strokes in young adults: 3% of all adult strokes, Stroke subtypes across the lifespan, Risk factor prevalence, Genetic causes of stroke, Ischemic stroke mechanism subtypes in young adults, Selected inflammatory arteriopathies, Arteriopathies due to vasospasm and abnormal vasoregulation, Cardiac embolism, Transcardiac embolism, Hypercoagulable states and hematologic disease, Mitochondrial encephalopathy, lactic acidosis, stroke-like episodes (MELAS), Intracerebral hemorrhage in young adults, Clinical features, Differential diagnosis of subarachnoid hemorrhage in the young adult, Work-up of the young stroke patient, Laboratory tests, Cardiac evaluation, Imaging, Additional tests, Prognosis, Treatment: diverse
Archived at 2021/03/30